INDUCTANCE VALIDATION OF LCR METER AFTER RECALIBRATION - Lukluk Khairiyati; Muhammad Azzumar; Miftahul Munir; Mohamad Syahadi (LIPI Press, Anggota IKAPI, 2021)
Laboratory of National Measurement Standard for Electricity and Time (NMS ET Lab) has validated the measurement results pre and post the LCR meter recalibration process on inductance parameters. The validation process was carried out at nominal values of 100 μH, 1 mH, 10 mH, 100 mH and 1 H in accordance to the reference standards. The direct measurement method was used to measure the inductance parameter of LCR meter with standard inductor. Validation is carried out by comparing the measurement results pre and post the LCR meter recalibration process at SCL - Hong Kong. Based on the En number analysis, the values between -0.21 to 0.44 were obtained for 5 measurement points, therefore the calibration system and method used by NMS ET Lab are valid and have measurement results that are equivalent to other countries.